An SNP-based diagnostic method for Brucella S2 vaccine strain infections - Wang, Xingya; Tian, Xiaowei; Li, Wanyang; Yang, Yuanchao; Zhang, Shuai; Wang, Hui; Geng, Wanru; Zhai, Jingbo (Frontiers in Veterinary Science, 2025)
BackgroundBrucellosis, a zoonotic bacterial infection caused by Brucella species, exhibits a global distribution. The Brucella S2 vaccine strain is known to cause brucellosis. Current serological antibody assays cannot distinguish between infections caused by the S2 strain and those caused by wild-type Brucella.ObjectiveTo develop a diagnostic method capable of specifically detecting S2 vaccine strain infections.MethodsTwo probes were designed targeting single nucleotide polymorphism (SNP) loci upstream of the sugar ABC gene; quantitative polymerase chain reaction (qPCR) and droplet digital polymerase chain reaction (ddPCR) methods were established. The performances of these methods were evaluated. The transient stem-loop structure of the DNA template was predicted, and the impact of probe overlap with the transient stem-loop structure on detection sensitivity was analyzed. Clinical applicability was assessed using 50 blood samples from brucellosis patients.ResultsBoth types of methods demonstrated high specificity. However, MGB-SNPdd showed greater sensitivity than other detection methods. Reduction of overlap between the probe sequence and the transient stem-loop structure enhanced detection sensitivity. In the clinical applicability analysis, ddPCR methods exhibited higher rates of S2 vaccine strain detection compared with qPCR methods.ConclusionSNP-based ddPCR methods demonstrate higher sensitivity than qPCR methods and enable specific detection of brucellosis caused by the S2 vaccine strain. Reduction of probe overlap with the transient stem-loop structure improves detection sensitivity, providing valuable insights for enhanced PCR amplification efficiency.